A song of power and the power of song essays on the book of Deuteronomy - Christensen, Duane L. 1938- (Winona Lake, IN Eisenbrauns, 1993)
Includes bibliographical references and indexes.
Keywords: Bible. O.T. Deuteronomy -- criticism, interpretation, etc